Up and running with deep learning (O'Reilly Media, 2016)
"Quickly dive-in to the most current topics in the field of deep learning, with this curated collection from Strata + Hadoop World 2016. This video features presentations from speakers in both academia and industry, covering the essentials of deep learning, and how to use the latest tools and techniques."--Resource description page.